Sistem Pendukung Keputusan Penentuan Kualitas Tempe Siap Jual Dengan Metode Weight Product - Benyamin Sembiring; Sulindawaty Sulindawaty (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2020)
According to this SNI, soybean tempeh is packaged in well-closed packages, namely leaves and plastic. At MSME Latersia Berkat Tempe, it was found that information problems determining the quality of tempe were very diverse in determining the quality of tempe, generally using traditional methods. In this study, the calculation was carried out by applying the SPK with the Weighted Product (WP) method in determining the quality of ready-to-sell tempe and designing the Decision Support System (SPK) application with the Weighted Product (WP) method in determining the quality of ready-to-sell tempe using Visual Studio 2010. Analysis of the data obtained Tempe data as alternative data is taken from general packaging, namely Tempe Wrapped in Plastic and Tempe Wrapped in Leaves. The criteria for determining the quality of tempe production, in this study are influenced by Raw Material (C1), Type of Yeast (C2), Packaging (C2), Taste (C4), Color (C5), Typical Odor of Tempe (C6), Texture (C7), Sales (C8). In the application, the Alternative Data and Criteria Data are inputted, then the calculation process is carried out using the Weighted Product method. The result of the WP ranking calculation is determined to be the highest value to be the final decision of the system.